Managing organic resources in agriculture: future challenges from a scientific perspective - Velthof, Gerard L.; Cals, Twan C. A.; van 't Hull, Jordy P.; Lesschen, Jan Peter; Lessmann, Malte; Porre, Rima J.; Ros, Mart B. H.; Rietra, René P. J. J.; Schoumans, Oscar F.; Veenemans, Lotte; Westerik, Dorien (Frontiers in Sustainable Food Systems, 2024)
Recycling of organic resources into agriculture has the potential to greatly increase nutrient use efficiency and improve soil carbon balance, but improper management can have adverse effects on the environment. Agriculture therefore faces large challenges to increase yields while decreasing these emissions to the environment. In this paper, we review i) the availability and composition of organic resources, ii) their agronomic value and risk of emissions, iii) potential measures to reduce their emissions, and iv) future challenges to support farmers and policy makers. The total amount of organic resource applied to soil amounted on average 41 kg nitrogen per ha agricultural land, 9 kg phosphorus per ha, and 456 kg carbon per ha in EU-27 + UK in 2017. Solid pig and cattle manures and cattle slurry are the most used organic resources. The availability of new organic resources from food processing, sewage sludge, municipal bio-wastes, and upcoming manure treatment techniques as fertilizer or soil conditioner is expected to strongly increase over the coming decade. Insight is needed into the composition of organic resources, the plant-availability of nutrients, the degradability of organic matter and the presence of contaminants. Measurement techniques become available to characterize soils, manures, crops, and emissions to the environment. However, the interpretation, and integration of data, and recommendations to farmers and policymakers using large amounts of data is expected to become more and more challenging. Many measures are available to improve nutrient and carbon management and to reduce emissions, including proper application, technological measures and structural changes in agriculture. For many measures, there is a risk of trade-offs that could lead to pollution swapping at different scales. We should focus on finding synergies between measures and no-regret management choices to develop effective mitigation strategies. The main future challenge for managing organic resources in agriculture is the development of an integrated nutrient management approach, including i) the characterization of organic resources, their agronomic value and their environmental risks, ii) knowledge of potential synergies and trade-offs between management measures, and iii) implementation of this knowledge into decision support tools, models and legislation to support farmers and policy makers.